TRANSRECTAL ULTRASONOGRAPHY OF EQUINE LUMBOSACRAL NERVES: PILOT STUDY IN 28 HEALTHY WARMBLOOD HORSES. Issue 2 (6th December 2016) - Espinosa, Pablo; Benoit, Philippe; Salazar, Isabel; de la Fuente, Jesús; Heiles, Philippe
Abstract : A noninvasive method for visualizing lumbosacral nerves would be helpful for horses with suspected lumbosacral plexopathy or injury. The aim of this prospective descriptive pilot study was to characterize the ultrasonographic appearance of the lumbosacral nerves in a sample of healthy horses, and expand on the technique for image acquisition. Horses were recruited for inclusion if they were determined to be healthy and sound based on clinical and lameness evaluation. Transrectal ultrasound images of the lumbosacral nerves (L6, S1, and S2) were obtained for both sides. Landmarks for localization, and techniques for nerve identification and measurement were described. Effects of sex, age, side, and nerve on measured thickness were statistically tested. Twenty‐eight warmblood horses were sampled (15 males and 13 females). Ages ranged from 5 to 15 years. Ventral nerve roots from L6 to S2 appeared as tubular structures with a characteristic hyperechoic linear echo pattern. There was no significant difference in nerve vertical diameter between left and right sides. A three‐way interaction was found among sex, age and lumbosacral nerve. The L6 nerve in males was significantly larger than S1 only in the youngest group. The S2 nerve was significantly smaller than L6 or S1 regardless of age group or sex. In conclusion, transrectal ultrasound was a feasible method for visualizing and measuring equine lumbosacral nerves. Wide ranges of sizes for each nerve were found between horses, however nerves were bilaterally symmetrical within horses. Side comparison is therefore recommended when nerve pathology is suspected.